2004
DOI: 10.1096/fj.04-2285fje
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAPK is required for Bax translocation to mitochondria, cytochrome c release and apoptosis induced by UVB irradiation in human keratinocytes

Abstract: This study establishes that activation of p38 MAPK by UVB represents a crucial signal required for the conformational change and translocation of Bax to the mitochondria in human keratinocytes. UVB-induced Bax translocation and mitochondrial cytochrome c release, which precede caspase activation and other endpoints of the apoptotic program such as chromatin fragmentation and loss of mitochondrial transmembrane potential, are blocked by genetic or pharmacological inhibition of the p38alpha MAPK. Inhibition of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
97
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(121 citation statements)
references
References 54 publications
21
97
2
1
Order By: Relevance
“…As a modulator of E-box-binding transcription factors, Id3 could potentially regulate the transcription of bax; the presence of 4 E-box elements in the human bax promoter supports this possibility (Mitchell et al, 2000). In any case, our results with HPV16 E6/7 immortalized cells are consistent with those of previous studies in which Bax induction by UVB was found to occur by both p53-dependent and -independent pathways (Shiloh, 2003;Van Laethem et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a modulator of E-box-binding transcription factors, Id3 could potentially regulate the transcription of bax; the presence of 4 E-box elements in the human bax promoter supports this possibility (Mitchell et al, 2000). In any case, our results with HPV16 E6/7 immortalized cells are consistent with those of previous studies in which Bax induction by UVB was found to occur by both p53-dependent and -independent pathways (Shiloh, 2003;Van Laethem et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, Bcl2 overexpression in HaCaT cells blocks the effects of UVB-induced Bax activation, cytochrome c release and apoptosis. UVB-induced DNA damage can upregulate Bax via p53-dependent or p53-independent pathways (Shiloh, 2003;Van Laethem et al, 2004). We next examined the involvement of the proapoptotic Bax in the Id3-induced death response by immunofluorescent staining of cells with antibodies that recognize the active form of Bax.…”
Section: Uvb Upregulates Id3 Expression In Hpv16mentioning
confidence: 99%
“…In contrast, Nakayama et al reported that p38 did not participate in VacA-induced cytochrome c release and Bax activation in gastric epithelial cells [38]. However, several studies have demonstrated that p38 MAPK activates Bax to induce mitochondrial cytochrome c release and apoptosis in neuroblastoma cells [39], keratinocytes [40], and lens epithelial cells [41]. Therefore, the mechanisms for p38-associated cytochrome c release and Bax activation in eosinophils appear to be cell-specific and different from those in gastric epithelial cells.…”
Section: Discussionmentioning
confidence: 93%
“…The conformational change and redistribution of Bax from the cytoplasm to the outer mitochondrial membrane induces mitochondrial cytochrome c release and is of major importance in UVB-induced apoptosis. 9 Recently, it has been shown that p38 MAPK is required for the UVB-induced Bax conformational change and translocation. 9 In keratinocytes, the b1-integrins mediate adhesion to the extracellular matrix, and also regulate the initiation of terminal differentiation and cell-detachment apoptosis or anoikis.…”
Section: General Features Of Keratinocyte Apoptosis and Cornificationmentioning
confidence: 99%
“…9 Recently, it has been shown that p38 MAPK is required for the UVB-induced Bax conformational change and translocation. 9 In keratinocytes, the b1-integrins mediate adhesion to the extracellular matrix, and also regulate the initiation of terminal differentiation and cell-detachment apoptosis or anoikis. Epidermal keratinocytes differentiate when they detach from the basement membrane and migrate to the suprabasal layers.…”
Section: General Features Of Keratinocyte Apoptosis and Cornificationmentioning
confidence: 99%